Teaching in Secondary School before the challenge of emotions: socio-emotional competence of the teacher to educate an active citizenship - Llorent-Vaquero, Mercedes; Mac Fadden, Isotta; Llorent-Bedmar, Vicente (IJERI: International Journal of Educational Research and Innovation, 2018)
In today’s society it seems to be essential to invest in education for an active citizenship that favors social cohesion, through the global development of the person. In this sense, educational agents have the responsibility to promote active learning that puts the importance of socio-emotional skills at the forefront. In this direction, socio-emotional education -oriented to learn to know, to do, to live together, to be- seems to offer the tools for the full development of the person. The main objective of this article is to deepen the current situation of socio-emotional competences in school contexts. For this, a pilot study has been carried only in two Secondary Education Institutes of Seville, where the final participant sample has reached 44 professors. It should be noted that this study is being carried out within the framework of the secondary school research project (Baccalaureate) in Morocco and Spain, funded by the Ministry of Foreign Affairs.